Development of Semiotic Assessment Instruments Based on Mathematical Literacy: Assessment Innovation in the Independent Curriculum - Hersiyati Palayukan; Muhammad Ikram; Landy Elena Sosa Monguel; Dilanalfita Sari (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study develops a semiotic assessment instrument based on mathematical literacy as an innovative evaluation tool aligned with the Independent Curriculum. The research addresses the lack of instruments capable of comprehensively measuring students’ ability to interpret and apply mathematical symbols in meaningful contexts. Using the Borg & Gall Research and Development (R&D) model, the study followed systematic stages including needs analysis, design, expert validation, testing, and refinement. Data from 180 grade VIII students showed that 68.3% faced challenges in interpreting mathematical symbols, emphasizing the need for such an instrument. The developed instrument consists of 25 items categorized into symbol comprehension, conceptual interpretation, and contextual application. Expert validation indicated strong alignment (82–88%), with construct validity of 67% and a reliability coefficient of 0.78. Regression analysis demonstrated a significant positive correlation (r = 0.76, p < 0.01) between semiotic interpretation and problem-solving performance. Integrating Peirce’s semiotic theory and mathematical literacy principles, the instrument provides a holistic framework for evaluating students’ symbolic reasoning and supports curriculum goals focused on meaningful mathematical understanding.